2003
DOI: 10.1086/375779
|View full text |Cite
|
Sign up to set email alerts
|

Detection of OH Absorption against PSR B1849+00

Abstract: We have searched for OH absorption against seven pulsars using the Arecibo telescope. In both OH mainlines (at 1665 and 1667 MHz), deep and narrow absorption features were detected toward PSR B1849+00. In addition, we have detected several absorption and emission features against B33.6+0.1, a nearby supernova remnant (SNR). The most interesting result of this study is that a pencil-sharp absorption sample against the PSR differs greatly from the large-angle absorption sample observed against the SNR. If both t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…It has been argued that even with existing telescopes like GBT, Arecibo and Parkes it should be possible to detect the OH line from black-widow and red-back pulsars (Ray & Loeb 2015). Such lines in absorption spectroscopy or maser emission in the (ISM) has already been detected for a few pulsars (Stanimirović et al 2003;Weisberg et al 2005;Minter 2008). …”
Section: Black-widows and Red-backs : Super-jupiter Companionsmentioning
confidence: 77%
“…It has been argued that even with existing telescopes like GBT, Arecibo and Parkes it should be possible to detect the OH line from black-widow and red-back pulsars (Ray & Loeb 2015). Such lines in absorption spectroscopy or maser emission in the (ISM) has already been detected for a few pulsars (Stanimirović et al 2003;Weisberg et al 2005;Minter 2008). …”
Section: Black-widows and Red-backs : Super-jupiter Companionsmentioning
confidence: 77%
“…The two previous large searches for OH absorption against pulsars by Stanimirović et al (2003) and Weisberg et al (2005) selected their targets based on the brightness of the pulsars. This yielded a detection rate of 2 out of 25 (8%), which motivated me to look for better selection criteria for pulsars with OH absorption.…”
Section: Source Selectionmentioning
confidence: 99%
“…Both Stanimirović et al (2003) and Weisberg et al (2005) observed numerous bright pulsars, 25 in total. In both cases, the OH absorption seen toward the pulsars have unique properties.…”
Section: Introductionmentioning
confidence: 99%
“…The observing and data processing procedures were very similar to Stanimirović et al (2003), who measured pulsar OH absorption profiles at Arecibo with the same back end, the Caltech Baseband Recorder. We had four observing sessions: 2000 August, 2000 December, 2001 September, and 2001 November, searching for H i absorption profile variations over time intervals from less than a day to 1.25 yr. Data from Frail et.…”
Section: Observations and Data Processingmentioning
confidence: 99%